Reinforced hydrogel network building by a rapid dual-photo-coupling reaction for 3D printing. Issue 14 (26th January 2023) - Zhou, Renjie; Hua, Yujie; Yang, Lipeng; Bao, Bingkun; Lin, Qiuning; Zhu, Linyong
Abstract : Based on photoinduced S -nitrosylation and Schiff base reaction, a novel hydrogel fabrication strategy has been established to rapidly construct reinforced, biocompatible hydrogels for 3D printing and for related biomedical applications. Abstract : A facile hydrogel fabrication strategy based on a simultaneous dual-photo-coupling reaction ( i.e., photoinduced S -nitrosylation and Schiff base reaction) was reported. This strategy allowed a strengthened three-arm crosslinking network to form in one step and the hydrogels obtained displayed rapid gelation, excellent mechanical strength and biocompatibility for cell encapsulated-3D printing in real time. Our hydrogel fabrication strategy will likely foster advances in biomaterials and the extreme speed and reinforced mechanical strength should significantly benefit 3D printing and related applications.